Age Differences in Leadership Positions Across Cultures - Vaughan-Johnston, Thomas; Imtiaz, Faizan; Lee, Albert; Ji, Li-Jun (Frontiers in Psychology, 2021)
In most countries around the world, the population is rapidly aging. A by-product of these demographic shifts is that older adults will likely occupy more positions of power and influence in our societies than ever before. Further, cultural differences might shape how these transitions unfold around the globe. Across two studies, we investigated whether business and political leaders differed in age across various cultures. Study 1 (N = 1,034) showed that business leaders were significantly older in Eastern (e.g., China, India, Japan) cultures than Western (e.g., United States, Sweden, United Kingdom) cultures, even while controlling for population structure (i.e., percentage of elderly in the society), gross domestic product (GDP), and wealth distribution across the population (GINI). Study 2 (N = 1,268) conceptually replicated these findings by showing that political leaders were once again older in Eastern versus Western cultures. Furthermore, cultural tightness mediated the relationship between culture and older leadership. These findings highlight how cultural differences impact not only our preferences, but also important outcomes in consequential domains such as business and politics. Potential explanations for why cultural tightness may be related to differences in leader age across cultures are discussed. To build on these findings, future research should assess the potential causal mechanisms underlying the cultural effect on leader age, and explore the various practical implications of this effect.